2012
DOI: 10.21608/mjfmct.2012.47769
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identification from Maxillary Sinus Using Multi-Detector Computed Tomography

Abstract: Attia et al ... been used for sexing the individual as bones of the body are last to perish after death, next to enamel of teeth (Deshmukh and Deversh, 2006). Radiography is used in forensic pathology for the identification of humans especially in cases where the body is decomposed, fragmented, or INTRODUCTlON Identification of skeletal and decomposing human remains is one of the most difficult skills in forensic medicine. Sex determination is also an important problem in the identification. Skeletal remains h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 1 publication
3
19
0
Order By: Relevance
“…In this study, while a significant sex difference was found in the length and height of maxillary sinus, there was no significant difference between sexes in maxillary sinus width. These results were in line with the findings reported by Fernandes et al In accordance with the current study, Attia et al found statistically insignificant lower values for maxillary sinus width between males and females. On the other hand, according to the results achieved in some previous studies, when compared with females, males had significantly wider maxillary sinuses .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, while a significant sex difference was found in the length and height of maxillary sinus, there was no significant difference between sexes in maxillary sinus width. These results were in line with the findings reported by Fernandes et al In accordance with the current study, Attia et al found statistically insignificant lower values for maxillary sinus width between males and females. On the other hand, according to the results achieved in some previous studies, when compared with females, males had significantly wider maxillary sinuses .…”
Section: Discussionsupporting
confidence: 94%
“…In this study, among the measured parameters, the maxillary sinus height was the best discriminating variable for sexual dimorphism. Uthman et al and Attia et al showed that the maxillary sinus height was the best discriminating variable which was consistent with our study. However, Ahmed et al indicated that maxillary sinus width was the best discriminant parameter.…”
Section: Discussionsupporting
confidence: 93%
“…study concluded that maxillary sinus dimension measurements, especially the right height, are valuable in studying the sexual dimorphism with overall accuracy 69.9%. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…They provide an accurate assessment of the paranasal sinuses, craniofacial bones, as well as the extent of pneumatization of the sinuses. [ 4 ] It provides detailed information that is not available from standard radiographs. [ 5 ] CT measurements of maxillary sinuses are useful to support gender determination.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In view of that, there are a number of studies stating the importance of maxillary sinuses in forensic medicine, especially for gender determination, where the dimensions of sinuses between males and females are compared by means of various imaging methods. [5][6][7][8][9][10][11][12][13][14] The results of most of these studies suggested the utility of the maxillary sinuses in gender determination. Almost all these studies reported that the sinus measurement values (dimensions and volume) are larger in males than in females and they correlated this fact with the differences in the overall stature of males and females.…”
Section: Introductionmentioning
confidence: 99%